Redesigning Care for the Management of Postpartum Hypertension: How Can Ob–Gyns and Primary Care Physicians Partner in Caring for Patients after a Hypertensive Pregnancy? - Berhie, Saba H.; Little, Sarah E.; Shulkin, Jay; Seely, Ellen W.; Nour, Nawal M.; Wilkins-Haug, Louise (American Journal of Perinatology, 2023)
The standard care model in the postpartum period is ripe for disruption and attention. Hypertensive disorders of pregnancy (HDPs) can continue to be a challenge for the postpartum person in the immediate postpartum period and is a harbinger of future health risks. The current care approach is inadequate to address the needs of these women. We propose a model for a multidisciplinary clinic and collaboration between internal medicine specialists and obstetric specialists to shepherd patients through this high-risk time and provide a bridge for lifelong care to mitigate the risks of a HDP.Key Points
Keywords: disparity; postpartum hypertension; innovation; hypertensive disorders of pregnancy